Semeadura direta e plantio de mudas para recuperação de nascentes no rio Piauitinga-SE - Oliveira, Andreza dos Santos (2013)
Due to the intense suppression of native vegetation in nascent areas of the State of Sergipe, one can notice a significant environmental degradation. Thus, it becomes necessary the adoption of practices aimed at the restoration of the vegetation and these can be carried through artificial regeneration with direct seeding or planting seedlings. Therefore, the study was carried to evaluate the development of native species in the Piauitinga watershed in Salgado-SE, with the artificial regeneration methods (direct sowing and planting seedlings), using the native forest species Anadenanthera macrocarpa (Benth.) Bren, Ceiba speciosa (A. St. Hill), Hymenaea stigonocarpa (Mart.) Hayne, Psidium guajava L. and Tabebuia aurea (Manso) Benth. & Hook. Initially, were held the physical and physiological quality of the seeds analysis in laboratory and subsequently a field experiment was established in a randomized block delimitation (RBD) in a factorial design with four replications, in an area previously occupied by pasture, located in Salgado-SE. The sowing was carried in holes (30x30x30cm), with spacing of 1,5 m x 1,5 m with 9 plants for species in every block and the planting of seedlings occurred similarly, totaling 90 plants per block, occupying an area of 0,1024 hectares. Were evaluated the percentage of emergence and seedling survival in the field, the initial development of seedlings and Relative Growth Rate (RGR) until 300 days after implantation. The species that showed better rates of emergence and survival was H. stigonocarpa with 74,44% and 48,89% respectively. Any plant of A. macrocarpa survived. In the of characteristics evaluation of growth in the field in relation to tillage, there was greater growth in height for P. guajava (25,84 cm) and diameter, T. aurea (6,51 mm). In planting seedlings, the more growth on the height was in the C. speciosa (93,26 cm) and the specie T. aurea presented greater increment in diameter (20,92 mm). There was statistical difference in the RGR of plants for planting two strategies. The species T. aurea, C. speciosa and H. stigonocarpa characteristics presented viable for use by direct seeding and planting seedlings in the recuperation of degraded areas of nascent. The strategy of planting that had higher averages for the parameters evaluated was the planting of seedlings in recuperation of the area studied.